A strategic study of acupuncture for diabetic kidney disease based on meta-analysis and data mining - Yu, Yunfeng; Hu, Gang; Yang, Xinyu; Yin, Yuman; Tong, Keke; Yu, Rong (Frontiers in Endocrinology, 2024)
Objective: The specific benefit and selection of acupoints in acupuncture for diabetic kidney disease (DKD) remains controversial. This study aims to explore the specific benefits and acupoints selection of acupuncture for DKD through meta-analysis and data mining. Methods: Clinical trials of acupuncture for DKD were searched in eight common databases. Meta-analysis was used to evaluate its efficacy and safety, and data mining was used to explore its acupoints selection. Results: Meta-analysis displayed that compared with the conventional drug group, the combined acupuncture group significantly increased the clinical effective rate (risk ratio [RR] 1.35, 95% confidence interval [CI] 1.20 to 1.51, P < 0.00001) and high-density lipoprotein cholesterol (mean difference [MD] 0.36, 95% CI 0.27 to 0.46, P < 0.00001), significantly reduced the urinary albumin (MD –0.39, 95% CI –0.42 to –0.36, P < 0.00001), urinary microalbumin (MD –32.63, 95% CI –42.47 to –22.79, P < 0.00001), urine β2-microglobulin (MD –0.45, 95% CI –0.66 to –0.24, P < 0.0001), serum creatinine (MD –15.36, 95% CI –21.69 to –9.03, P < 0.00001), glycated hemoglobin A1c (MD –0.69, 95% CI –1.18 to –0.19, P = 0.006), fasting blood glucose (MD –0.86, 95% CI –0.90 to –0.82, P < 0.00001), 2h postprandial plasma glucose (MD –0.87, 95% CI –0.92 to –0.82, P < 0.00001), total cholesterol (MD –1.23, 95% CI –2.05 to –0.40, P = 0.003), triglyceride (MD –0.69, 95% CI –1.23 to –0.15, P = 0.01), while adverse events were comparable. Data mining revealed that CV12, SP8, SP10, ST36, SP6, BL20, BL23, and SP9 were the core acupoints for DKD treated by acupuncture. Conclusion: Acupuncture improved clinical symptoms, renal function indices such as uALB, umALB, uβ2-MG, and SCR, as well as blood glucose and blood lipid in patients with DKD, and has a favorable safety profile. CV12, SP8, SP10, ST36, SP6, BL20, BL23, and SP9 are the core acupoints for acupuncture in DKD, and this program is expected to become a supplementary treatment for DKD.